Developing A Blended Finance Implementation Model For Community Empowerment In Rural Areas - Zainal Abidin; Aden Apandi (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Objective: This study analyzes the implementation of blended finance in four rural areas in Indonesia: Gekbrong (Cianjur, West Java), Ulubelu (Tanggamus, Lampung), Sungai Kakap (Kubu Raya, West Kalimantan), and Kahayya (Bulukumba, South Sulawesi). Methodology/approach: Using a funding source mapping and needs analysis approach, this study evaluates the assistance program provided to beneficiaries through various funding sources and examines how these programs can increase their capacity and strengthen their economies. Findings: This study introduces a new scheme for community empowerment that integrates various funding sources with a ranking system to assess the conditions of beneficiaries. It also shows that blended finance has succeeded in increasing the productivity of vegetable farmers in Gekbrong, coffee farmers and livestock breeders in Ulubelu, chili farmers and fishermen in Sungai Kakap, and coffee farmers in Kahayya. Practical implications: Despite facing different challenges in each area, blended finance has proven effective in reducing the gap in access to capital and strengthening local economies. Originality/value: Other regions can adapt this model by implementing policies that encourage collaboration between government, financial institutions, and local communities. PT KMM plays a crucial integrator role in implementing this model.